The study on wavelet coefficient behavior of simultaneous fault on the hybrid between overhead and underground distribution system - Chaichan Pothisarn; Chaiyan Jettanasen (My University, 2019)
This paper proposed the study on behaviour and characteristic of wavelet coefficient in case of simultaneous fault occurrence on hybrid transmission system.The ATP/EMTP software has been used to simulate 115-km hybrid transmission line that modelled after on part of PEA distribution system.The case study system is 40 km distribution line with overhead line on first 20 km section and underground cable on the second half.The Discrete Wavelet Transform (DWT) has been used to analyse fault signal.Various factor that can affect system characteristic such as inception angle, location, and type of fault has been taken into consideration.The result shown the significant change in coefficient of high frequency component when simultaneous fault occurs compared to single fault especially in hybrid distribution system when fault occur on both overhead and underground cable, thus result in problematic analysis of coefficient and complexity in design suitable algorithm.This change in system characteristic must be taken into consideration when develop protection system in order to achieve the satisfactory performance with even more complex power system in the future.
Keywords: Power Systems Fault Detection